The basis risk of catastrophic-loss index securities - Cummins, J.David; Lalonde, David; Phillips, Richard D. (Journal of Financial Economics, 2004)
Using a windstorm simulation model developed by Applied Insurance Research, we analyze the effectiveness of catastrophic-loss index options in hedging hurricane losses for Florida insurers. The results suggest that insurers in the two largest size quartiles can hedge losses almost as effectively using contracts based on four intrastate indices as they can using contracts that settle on their own losses. Many insurers in the third largest size quartile also can hedge effectively using the intrastate indices, but most insurers in the smallest quartile would encounter significant basis risk. Hedging using a statewide loss index is effective only for the largest insurers.